Sustainable development of machine-building enterprises: influence of risk target parameters on innovative support - Sekirozh, Yaroslav (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article stipulates that machine-building enterprises in a market economy in the process of carrying out any business operations must take into account the fact of the probability of negative developments and their financial consequences. In order to avoid the global consequences of the manifestation of risks, companies must have a system for diagnosing the level of sustainability of development, taking into account the impact of target risk parameters and innovative support to prevent significant financial losses. The proposed algorithm of the methodological approach to determine the impact of target risk parameters on the level of innovative support for sustainable development of machine-building enterprises allows to take into account both the requirement to maximize the expected total income and the requirement to minimize variance, ie lower risk than expected. It is concluded that the algorithm makes it possible to identify and identify risks, ie to determine the portfolio of risks and the impact of innovation on their level and vice versa, which accompanies the implementation of appropriate management decisions and delineation of their scope. One of the components of the formation of mechanisms for diagnosing the level of innovative support for sustainable development of machine-building enterprises is risk management. The importance of this component increases with the increase in the cost of covering or compensating for the risks faced by machine-building enterprises. Evaluation of the results and adjustment of selected methods occurs after the implementation of these methods directly into the work of the enterprise. This stage is crucial because it allows to draw conclusions about the methods that have been used to neutralize or reduce risks, namely: whether they sufficiently protect the machine-building enterprise from potential threats, determine the level of reliability of certain methods and areas for improvement and adjustment. selected methods of diagnostics of the level of sustainable development of machine-building enterprises taking into account the target parameters of risk and innovation.